Efektivitas Kinerja Inspektorat Daerah dalam Melakukan Fungsi Pengawasan (Study Kasus Pada Pegawai Inspektorat Daerah di Kabupaten Mamberamo Tengah Provinsi Papua Pegunungan) - Rumidi Rumidi; Ngadisah Ngadisah; Renida Jozelina Toroby (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of supervision (Variable X1) on performance (Y). This research adopted a quantitative method with a coparative approach. Data collected through questionnaire distribution techniques. Data analysis techniques prioritize numerical analysis starting from data preparation, data tabulation to the hypothesis testing stage. Through linear regression analysis techniques, the results obtained are that if supervision increases, performance will also increase. The results of testing the coefficient of determination (R2) also show that performance is influenced by supervision by 49% while the remaining 51% is influenced by other variables outside this research, while the correlation test proves that there is the strong influence of supervision on performance. This evidence is also in line with the results of the t-test where the effect of supervision on performance is very positive and significant as proven through the t-test. Conclusion: Supervision has a significant effect on performance. Keywords: Performance Effectiveness, Supervision